Analysis of Differences in the Motivation of the Owner-Managers and Hired Managers of Regional Enterprises - Mukhacheva, Anna Valentinovna; Sokolov, Artem Igorevich (Economy of Regions, 2017)
The article deals with the differences in the motivation of owner-managers and hired managers. The purpose of the article is to identify the signs of the differences and similarities in the motivation of hired managers and owner-managers on the basis of the analysis of the results of the study of these issues by other authors, as well as with the help of our research. The hypothesis of the study consists in the assumption that the motivational profile of owner-managers differs from the motivational profile of hired managers in greater riskiness and thrift. The research methodology involves conducting a sociological survey of 100 managers of small and medium-sized enterprises in Kemerovo, half of which are employed and the other half are business owners. Questioning was carried out by several methods: oral, by e-mail, in writing through the Center for Business Support and through other means. The data we processed in the SPSS Statistic program. The results of the study unexpectedly have rejected a basic hypothesis: the average data for the degree of risk and thrift of hired managers is highly competitive with the received indices of owner-managers. There is the only difference in the distribution of characteristics. The level of riskiness and thrift of the hired managers tends to the be average among them and has a slight variation in the estimates, while the owner-managers much differ from each other on these parameters, have a large variation in the values of indicators, show a lot of the diametrically opposed estimates. The study of the motives of of owner-managers activity allows to the authorities to develop recommendations on the improvement of the existing and new programmes for the support of small and medium-sized business; on the formation of executive candidate pool. It also can contribute to revealing the categories of population with expressed entrepreneurial and managerial motivational profiles at a stage of professional education for their fastest involvement in effective work.